2008
DOI: 10.1002/aqc.954
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton size structure in transitional water ecosystems: a comparative analysis of descriptive tools

Abstract: ABSTRACT1. Individual size has important implications for the physiology and ecology of phytoplankton. The analysis of size structure is a common approach for studying structure and function of planktonic ecosystems, with applications for the monitoring and conservation of aquatic ecosystem health. Several ways to describe the size structure of phytoplankton communities are used, including size-abundance relationships (SAR), nonnormalized and normalized biomass size spectra (BSS), non-normalized and normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Such factors necessitate the need for a multi-metric index incorporating various phytoplankton, morphology and physicochemical attributes that can affect phytoplankton occurrence in riverine systems, in order to obtain a comparative assessment of nutrient load impacts. Notably, the current study would add to the literature of other studies that have indicated how the abundance distribution of the phytoplankton communities can vary significantly in relation to human-generated or environmental forcings (Sabetta et al 2008).…”
Section: ≤26mentioning
confidence: 82%
“…Such factors necessitate the need for a multi-metric index incorporating various phytoplankton, morphology and physicochemical attributes that can affect phytoplankton occurrence in riverine systems, in order to obtain a comparative assessment of nutrient load impacts. Notably, the current study would add to the literature of other studies that have indicated how the abundance distribution of the phytoplankton communities can vary significantly in relation to human-generated or environmental forcings (Sabetta et al 2008).…”
Section: ≤26mentioning
confidence: 82%
“…The Southern Adriatic/Eastern Ionian area is characterized by oligotrophic conditions and low primary productivity. Nutrient supply to the shelf area strongly depends on inputs of surface waters along the coast (which in the Salento Peninsula are more abundant in the Northern part) as well as on inputs of groundwater [ 52 ]. A superficial southward coastal current flowing from the Northern Adriatic basin and a deep north-westward current flowing from the Eastern Mediterranean (Levantine Intermediate Waters, LIW) also contribute to nutrient supply in the shelf area, although their influence on the Southern Adriatic basin is generally limited, on both temporal and spatial scales [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the frame of the WISER and ActionMed projects, (Lugoli et al, 2012;Sabetta et al, 2008;Vadrucci et al, 2013), minimising the problem of taxonomic expertise required, and allowing quantitative inter-calibration procedures (Carvalho et al, 2013).…”
Section: Review Of Phytoplankton Indicatorsmentioning
confidence: 99%